A subset of morphologically distinct mammary myoepithelial cells lacks corresponding immunophenotypic markers - Zhang, Roy R (BioMed Central, 2003)
INTRODUCTION: Immunostaining for smooth muscle actin (SMA) is commonly used to elucidate mammary myoepithelial (ME) cells, whose presence or absence is a reliable criterion for differentiating in situ and invasive carcinomas. However, some morphologically distinct ME cells fail to stain for SMA. This study intended to assess whether these SMA-negative cells also lack the expression of other ME cell markers. METHODS: Hematoxylin/eosin and SMA immunostained sections from 175 breast cancer patients were examined. Three cases were found to harbor ducts that showed morphologically distinct ME cell layers, but showed no SMA immunostaining in at least one-third of the layer or the entire layer. Eight additional consecutive sections from each case were stained for SMA, using a black chromogen, and each was then re-stained for one of eight additional markers supposed to exclusively or preferentially stain ME cells, using a red chromogen. SMA-negative ME cells were re-examined for the expression of other markers. RESULTS: SMA-negative ME cells in two cases also failed to display immunoreactivity for other markers, including calponin, CD10, smooth muscle myosin heavy chain, protease inhibitor 5 (maspin), Wilms' tumor-1, and cytokeratins 5, 14, and 17 (CK5, CK14, and CK17). However, in one case SMA-negative ME cells displayed immunoreactivities for maspin, CK5, CK14, and CK17. The distribution of these ME cells is independent of ductal size, length, and architecture. CONCLUSIONS: A subset of morphologically identifiable ME cells lack the expression of nine corresponding immunophenotypic markers, suggesting that ME cells might also be subject to different normal and pathological alterations.